RANCANG BANGUN ALAT UJI EMISI EKONOMIS MENGGUNAKAN SENSOR GAS MQ2 DAN MQ9 BERBASIS ARDUINO - Adzina Mukhlasin, Mohamad; Kholis, Nur; Eka Pramitasari, Retno (Reaktom : Rekayasa Keteknikan dan Optimasi, 2019)
Exhaust emissions generated by motor vehicles are increasing as the number of motor vehiclesincreases. Carbon monoxide (CO) and Hydro Carbon (HC) is harmful substance contained in exhaustemissions. This study aims to make emission test (prototype) to measure CO and HC levels on exhaustemissions. This type of research is an experimental research with the waterfall model design method.Arduino-based emission test (prototype) with working system of CO and HC concentration on emissionwill be read by MQ2 and MQ9 sensor connected with Arduino and displayed on lcd screen in digitalnumber using C language program. Further data on the prototype is taken and compared with the dataon the gas analyzer using the T Test method. The results of testing the CO and HC levels on emissiontest equipment (prototype) with the results of testing using a gas analyzer still showed a significantdifference with the significance value of CO level readings of 0.319 and HC levels of 0.896. Keywords: exhaust emissions, MQ2, MQ9, Arduino